(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency and mortality rate of stroke and its types in diabetic and non-diabetic patients of rural Sindh. Study Design: Descriptive / Observational study Place and Duration of Study: This study was conducted at the medical ward and out patient’s department, Peoples University of Medical and Health Sciences, Nawabshah from January 2016 to December 2016. Materials and Methods: This descriptive observational study was conducted on 74 cases of stroke. The patients were collected from medical ward and out patient’s department of Peoples Medical College Hospital as well as private clinics, 74 patients of acute stroke fulfilling the inclusion/exclusion criteria were included in the study. The clinical and demographic data obtained was collected on a proforma and results were tabulated. Results: 74 cases of stroke including 48 (64.9%) males were evaluated. Diabetes was diagnosed in 43 (58.1%) cases, among these74 cases 53 (71.6%) cases having ischemic stroke and 21 (28.4%) having hemorrhagic stroke. Majority of diabetic patients were male and having ischemic stroke. 06 (8.1%) non-diabetic cases died, majority of them were male with ischemic stroke, and 14 (18.9%) diabetic cases died among them majority were male having hemorrhagic stroke. As a whole 54 cases survive and the survival rate was more in patients of ischemic stroke. Conclusion: The ischemic strokes are more prevalent than hemorrhagic strokes especially in diabetic patients. The mortality rate was worse in cases of diabetes especially in hemorrhagic strokes. There is a need of early diagnosis and treatment of diabetes to avoid stroke and to improve prognosis in stroke.